2017
DOI: 10.3390/nu9030188
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Overweight and Obesity in Children and Adolescents from Migrant and Seasonal Farmworker Families in the United States—A Systematic Review and Qualitative Assessment

Abstract: Overweight and obesity (OW/OB) is a pressing health concern among migrant and seasonal farmworker (MSFW) families in the US. The limited number of previously reported research on MSFW families suggests that their unique sociodemographic characteristics and lifestyle predispose them to poor health outcomes including OW/OB. We aimed to synthesize and assess available data on the prevalence and modifiable health determinants of OW/OB in MSFW children and adolescents. Literature search, study selection, data extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
1
10
0
1
Order By: Relevance
“…In our patients, the prevalence of perinatal asphyxia both in the UA group and in the DE group exceeded the one observed in the average population of 0.5-1% (5-10:1000 births) (17). Several studies have shown that the BMI-SDS of the parents plays an important role influencing the BMI-SDS of a child (18). In the current study, maternal BMI-SDS was significantly higher in children with obesity compared to mothers of children with overweight.…”
Section: Discussionsupporting
confidence: 44%
“…In our patients, the prevalence of perinatal asphyxia both in the UA group and in the DE group exceeded the one observed in the average population of 0.5-1% (5-10:1000 births) (17). Several studies have shown that the BMI-SDS of the parents plays an important role influencing the BMI-SDS of a child (18). In the current study, maternal BMI-SDS was significantly higher in children with obesity compared to mothers of children with overweight.…”
Section: Discussionsupporting
confidence: 44%
“…The 18 review studies found (31)(32)(33)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) were examined to see if they provided primary data, otherwise they were discarded. The final number of manuscripts was 117.…”
Section: Manuscripts Examinationmentioning
confidence: 99%
“…Obesity is a fast-growing problem that is reaching epidemic magnitudes worldwide, affecting both children and adults (Ogden et al, 2016 ; Lim et al, 2017 ). This condition is defined as a disproportionate body weight for height with excessive fat accumulation that is frequently accompanied by mild, chronic, systemic inflammation (Gonzalez-Muniesa et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%